P003 APPLYING THE TRANSITION READINESS ASSESSMENT QUESTIONNAIRE TO AN UNDERSERVED ADULT INFLAMMATORY BOWEL DISEASE POPULATION. (7th February 2019) - Talat, Arslan; Radin, Arielle; Frangopoulos, Eve; Isono, Michela; Chen, Lea Ann
Abstract: Background: The Transition Readiness Assessment Questionnaire (TRAQ) is a 20-item, 5-domain, validated measure of preparedness for youths with chronic illnesses to transition into adult clinics. Each question is graded on a 1-5 scale, with higher scores indicating greater skill mastery. Studies of the TRAQ in pediatric inflammatory bowel disease (IBD) patients have suggested a score of 4.5 as the threshold for readiness for adult clinics and have furthermore highlighted the impact of language, race, and socioeconomic status on successful transitions. We hypothesized that the TRAQ can similarly be used to identify those who require additional education in healthcare engagement among socioeconomically-disadvantaged adult patients with IBD. Methods: As a part of routine clinical care, the TRAQ was administered to adults with IBD presenting to Bellevue Hospital, an academic public hospital in New York City. The written survey was offered in English, Chinese, or Spanish, or was read with a phone interpreter to patients who preferred another language. In a subset of patients, a second TRAQ was administered 6 months after the initial evaluation to assess for differences in patients' understanding and behavior over time. Demographic and clinical data were extracted from electronic medical records. Two-tailed, non-parametric t-tests were used to asses for differences between groups, with a threshold of p<0.05 set for statistical significance. Missing data or questions marked as "not applicable" by study subjects were omitted from analysis and denominators were lowered accordingly. Results: Sixty-five patients (63% male) completed the TRAQ survey (68% English, 15% Chinese and 17% Spanish) and scored an average of 4.37. The highest scoring domain was 'Managing daily activities' (MDA; 4.59), while the lowest was 'Tracking health issues' (THI; 3.879). Overall and for each domain, there was a lower average TRAQ score for non-English speaking patients compared to English speakers that was not statistically significant. Thirty-three individuals completed a second TRAQ survey in 6 months, with no significant change in mean scores. However, when these patients were stratified based on language, we found that scores of English speakers did improve (4.42 vs 4.67, p=0.01) while scores of Non-English speakers did not (4.11 vs 4.09, p=0.94). Conclusion: As expected, most adult IBD patients were successful in managing activities of daily living. However, almost half of the surveyed population did not reach the threshold of healthcare utilization mastery set for pediatric patients. While TRAQ scores improved in a subset of individuals, targeted education in "tracking health issues" with special attention to non-English speaking patients may be required to improve successful utilization of healthcare services in an underserved adult IBD population.